2023
DOI: 10.1109/tap.2023.3276508
|View full text |Cite
|
Sign up to set email alerts
|

Fully Probe-Corrected Near-Field Far-Field Transformations With Unknown Probe Antennas

Abstract: According to the electromagnetic uniqueness theorem, the radiation behavior of an antenna under test (AUT) can be recovered from measurements of two tangential components of its radiated fields on an enclosing surface. In practice, measurements conducted in the radiating near-field (NF) of an AUT utilize probe antennas of finite size. Thus, instead of discrete field values, spatially blurred probe signals are acquired. The probe influence can be compensated, however, this commonly requires precise knowledge ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Since the first experiment in 1900 by Flemming [1] and the first scientific theory in 1938 [2], the rectangular waveguide open-end radiator, as one of the canonical radiating elements, has been used in a wide range of applications, including near-field antenna measurement [3][4][5][6][7][8][9], dielectric material characterization [10,11], electric field measurement [12,13], array antennas [14][15][16], electric field probe calibration [17], feeding a reflector antenna [18], non-destructive testing [19][20][21], imaging sensors [22] and the excitation of various radiating elements [23][24][25][26]. A comprehensive review of various open-ended waveguides has been presented in [27].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first experiment in 1900 by Flemming [1] and the first scientific theory in 1938 [2], the rectangular waveguide open-end radiator, as one of the canonical radiating elements, has been used in a wide range of applications, including near-field antenna measurement [3][4][5][6][7][8][9], dielectric material characterization [10,11], electric field measurement [12,13], array antennas [14][15][16], electric field probe calibration [17], feeding a reflector antenna [18], non-destructive testing [19][20][21], imaging sensors [22] and the excitation of various radiating elements [23][24][25][26]. A comprehensive review of various open-ended waveguides has been presented in [27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, predicting a FF RCS from an NF extrapolation is an important research area. Recent studies have demonstrated that by processing the scattered EM field detected by a scanning probe around the target in the NF region, NF-to-FF transformation [1][2][3][4] (NFFFT) technology can predict the target's RCS in other regions.…”
Section: Introduction 1background and Motivationmentioning
confidence: 99%